Analysis of pilocytic astrocytoma by comparative genomic hybridization - Sanoudou, D.; Tingby, O.; Ferguson-Smith, M. A.; Collins, V. P.; Coleman, N. (Br J CancerBr J CancerBr J Cancer, 2000)
Very little is known about genetic abnormalities involved in the development of pilocytic astrocytoma, the most frequently occurring brain tumour of childhood. We have analysed 48 pilocytic astrocytoma specimens using comparative genomic hybridization. Only five of 41 tumours from children showed abnormalities detectable by comparative genomic hybridization, and in each case this represented gain of a single chromosome. Interestingly, two of seven tumours from adults showed abnormalities, which were multiple and relatively complex. Six of the seven tumours showing abnormalities were from female patients (two adults and four children). The most frequently detectable abnormality was gain of 9q34.1-qter, which was present in three cases (two adult and one paediatric).
Keywords: Adolescent; Adult; Astrocytoma/*genetics/physiopathology; Brain Neoplasms/*genetics/physiopathology; Child; Child, Preschool; Chromosome Aberrations/*genetics; Female; Gene Duplication; Humans; Infant; Infant, Newborn; Male; Nucleic Acid Hybridization